Seleção de agentes de controle biológico contra Stromatinia cepivora - Cândido, Vanessa Carvalho (2019)
Stromatinia cepivora Whetzel (Syn. Sclerotium cepivorum Berk.), which causes the disease known as white rot, affects garlic-producing areas worldwide and causes severe losses. The pathogen has a restricted host range, exclusively attacking plants in the genus Allium and is capable of forming sclerotia, which are responsible for the spread of the pathogen that occurs at temperatures around 17°C. Sclerotia can remain viable in the soil for 20 years in the absence of host plants. The application of antagonistic microorganisms in the field to control pathogens is considered a sustainable alternative for disease management. In this context, the search for alternative measures that can assist in the effective control of the disease is desirable. The objective of this study was to select biological control agents against S. cepivora that are capable of colonizing and degrade the sclerotia at 17°C, the temperature in which the incidence of the disease is higher. Seventy isolates from different localities were evaluated. The mycelial growth and sporulation capacity of the isolates were verified by plating each isolate in PDA medium and incubating for 7 days at 17°C. The “in vitro” assays were performed by applying 2 microliters of the spore suspension of each isolate on eight sclerotia placed on wet filter paper inside Petri plates incubated at 17°C for 14 days. After this period, the sclerotia were sterilized again and plated in a new plate containing PDA medium and incubated at 17°C for 20 days to verify sclorotia viability. Fifty-one isolates grew and sporulated at 17°C, which are promising characteristics for the development of biological control products. Trichoderma isolates CX01TR12-, CX01TRCAM and CX02TR19MTS colonized 100% of the sclerotia in both times the experiment was performed. These isolates have the potential to be tested in future field experiments to control S. cepivora in garlic.